PERMASALAHAN DAN HARAPAN DALAM IMPLEMENTASI KURIKULUM 2013 - ,, Krisdayanti (rc-institut, 2019)
The research was backed by the many problems that arise due to changes in the curriculum from KTSP to Curriculum 2013, especially the problems felt by the teacher. These problems cause the implementation of the curriculum 2013 to be difficult to realize. This research is a qualitative descriptive study. The results of this study indicate that the problems perceived by the teacher lie in; (1) difficulties in making lesson plans because the teacher does not understand in writing the indicators of each of the basic competencies (KD). (2) the teacher still has not applied student-centered learning. (3) the inability of the domain of skills at KD-4. (4) the teacher feels overwhelmed in making an assessment. In order for this problem to be resolved, it is expected to be; (1) the implementation of 2013 Curriculum training. (2) simplification of the 2013 Curriculum assessment assessment, (3) the addition of facilities and infrastructure so that the implementation of basic competencies in the realm of skills can be carried out.